Method to Calculate Mining-Induced Fracture Based on the Movement and Deformation of Overburden Strata. (17th September 2021) - Xu, Guo-sheng; Li, Hui-gui; Li, De-hai; Zhang, Yan-bin
Abstract : Mining-induced fracture of overburden strata is intimately related to underground water disasters in coal mining. In this work, we develop an analytical model that uses the probability integral method to calculate the subsidence of the subsurface and the overburden strata. In the developed model, according to the failure characteristics of the mining-induced strata, the horizontal deformation of the strata is expressed by the tensile rate of the elastic plate's neutral plane to reflect the degree of fracture initiation and expansion. The distribution of the water-flowing fractured zone (WFZ) in the overburden strata is calculated by substituting the probability integral function of overburden strata movement into the equation of layer tensile rate. The panel 31071 in Peigou coal mine is taken as a case study, and the height of the water-flowing fractured zone ( H WFZ ) is determined by the proposed method. Conventional empirical methods and the proposed method are used to predict H WFZ in panels with mining schemes, and the results show that the model is particularly advantageous for inclined coal seam mining where the inclined mining size gradually increases and the coal seam burial depth gradually decreases. In such kind of situations, the overburden strata movement and deformation intensify and the mining fracture develops further with the progress of mining, a feature considered poorly by conventional empirical methods but well represented in the proposed method.